2011
DOI: 10.1007/s00018-011-0713-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of host-defence peptides in eye diseases

Abstract: The eye and its associated tissues including the lacrimal system and lids have evolved several defence mechanisms to prevent microbial invasion. Included among this armory are several host-defence peptides. These multifunctional molecules are being studied not only for their endogenous antimicrobial properties but also for their potential therapeutic effects. Here the current knowledge of host-defence peptide expression in the eye will be summarized. The role of these peptides in eye disease will be discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 140 publications
(154 reference statements)
0
39
0
Order By: Relevance
“…The therapeutic potential of AMPs has been actively studied in numerous bacterial infectious diseases, including skin infection, pneumonia, and peritonitis. However, few studies have focused on the topical application of naturally occurring AMPs to treat bacterial keratitis (12,17). In the current study, we investigated the potential application of a snake AMP (OH-CATH30) in ocular bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The therapeutic potential of AMPs has been actively studied in numerous bacterial infectious diseases, including skin infection, pneumonia, and peritonitis. However, few studies have focused on the topical application of naturally occurring AMPs to treat bacterial keratitis (12,17). In the current study, we investigated the potential application of a snake AMP (OH-CATH30) in ocular bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the synthetic peptide COL-1 demonstrated potent antimicrobial activity in vitro, but it was not effective in a rabbit model of P. aeruginosa keratitis and showed toxicity to rabbit corneas (19). Although the reason for the poor efficacy of the peptides in vivo is not well known, previous studies have demonstrated that the salt content of tears inhibits the antibacterial activity of some host defense peptides (12) the MPO in P. aeruginosa-infected mouse corneas, but it did not efficiently eradicate invading bacteria owing to its poor bactericidal activity against P. aeruginosa isolates in vitro (20). The protective efficacy of B-Lfcin in P. aeruginosa keratitis mainly depended on its anti-inflammatory properties and an increase in the antibacterial activity of CIP against multidrug-resistant P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vivo studies in a murine model of bacterial keratitis have shown that deficiency (either by transient silencing by short interfering RNA [siRNA] or gene knockout [KO]) of mouse ␤-defensin 2 (mBD2) or mBD3 (homolog of human ␤-defensin 2) or the cathelicidin cathelin-related antimicrobial peptide (CRAMP) (homolog of human LL37) results in more severe infection and tissue damage (23)(24)(25)(26). Further, exposure to Candida albicans significantly upregulated the expression of CRAMP (27), and mice deficient in CRAMP were more susceptible to Candida keratitis than wild-type (WT) mice (28).…”
mentioning
confidence: 99%